The Development of Web-based Sales Reporting Information Systems using Rapid Application Development Method - Suryasari Suryasari; Jansen Wiratama; Ririn Ikana Desanti (Ultima InfoSys : Jurnal Ilmu Sistem Informasi, 2022)
Many studies can be used as references regarding the application of information systems in companies that can optimize business processes. Information Systems can be designed according to the needs of each company. Concerning the company, PT Artindo Pratama Sejahtera is a private company engaged in paint production. One of the problems in business processes at the company is when the sales report activity from the salesperson to the warehouse admin section needs to be recorded in the database because it still uses the short message/chat application media. In addition, the short messages/chats often pile up. Based on the literature review that has been done from previous research, these problems can be overcome by implementing an information system. The purpose and contribution of this research are to optimize business processes in reporting activities so that they become integrated. The output of this research is a website-based Sales Reporting Information System. Before the Information System was implemented at PT Artindo Pratama Sejahtera, functionality testing was carried out by system users using the User Acceptance Test (UAT) method with the black box testing model and obtaining results according to company needs so that they could overcome the problems described earlier.